Desenvolvimento de metodologia para determinação de resíduos de pesticidas em cupuaçu (Theobroma grandiflorum Schum) utilizando as técnicas de MSPD e HPLC-UV/DAD - Lima, Tamires Gleice de (2012)
Tropical fruits gaining ever greater consumer market, Brazil is the third largest producer. The consumption of fruits has increased significantly due to its organoleptic characteristics and high nutritional value. Among these fruits, economically important and highly appreciated in the Amazon region, there is cupuassu (Theobroma grandiflorum Schum.). The presence of pesticide residues in food can cause serious health risks, making it essential to the study of analytical methodologies for its determination. In the literature there is no record of analytical methodologies for determination of pesticides in cupuassu. Given this, the present work aims at developing a methodology for the determination of pesticides bromuconazole, fenbuconazole, kresoxim-methyl and teflubenzuron in cupuassu, using as a technique for extracting the scattering matrix solid phase (MSPD) and analysis by high performance liquid chromatography with UV-Vis detector with diode array. The method by dispersing the solid phase matrix was carried out, by testing different types of adsorbents (neutral alumina, florisil, silica and C18) and organic solvents (10 and 20 mL) dichloromethane, acetone for the elution. The best results for the recovery of pesticides were obtained with 20 mL of dichloromethane: acetone (9:1, v / v) using a neutral alumina as adsorbent, with recovery values of between 64.0 and 110%, with coefficients variation in the range from 3.5 to 17.1% at levels of concentration (0.5, 1.0 and 2.0 μg g-1). The correlation coefficients of standard curves were between 0.9996 and 0.9998, the values of the limits of detection (LOD) and quantitation (LOQ) were in the range between 0.1 and 0.3 μg g-1, and 0,5 μg g-1, respectively. The repeatability was less than 12.3% and intermediate precision was less than 11,0%.